The problem of justice and the duty of a warrior in the interpretation of the Bhagavad-Gita - Matvieiev, Vitalii; Dobrodum, Olga (Skhid : analitychno-informat͡s︡iĭnyĭ z͡h︡urnal, 2025)
The article examines the problem of justice and the duty of the warrior in the interpretation of the "Bhagavad-Gita" - a sacred text that is part of the Indian epic "Mahabharata." Particular attention is given to issues related to life, death, and the fulfillment of duty, i.e., following one's dharma, which should ultimately lead to spiritual perfection and liberation from samsara (the cycle of birth and death). The central element of the "Bhagavad Gita" is the discussion of the problems of war and peace, presented through the dialogue between Prince Arjuna and the god Krishna on the battlefield of Kurukshetra. The authors of the article analyze the philosophical reflections presented in the "Bhagavad-Gita" on how a person can find peace and satisfaction in a world full of conflicts by following true yoga. The article points out that the "Bhagavad Gita" also draws attention to the moral aspects of war, emphasizing the importance of a just struggle. Krishna teaches that the struggle must be just and that the sacrifices of war should not be in vain. Krishna explains to Arjuna that fighting is not an immoral act if it is done in accordance with the duty (dharma) of a warrior. The duty of a warrior is to protect truth and righteousness, even if it requires participating in battle. Krishna emphasizes that war should be the result of higher goals, such as restoring justice and order, and not for personal ambitions, profit, or revenge. The article emphasizes that the war in the "Bhagavad-Gita" is viewed as a necessary part of the universal process, in which it is important for everyone to impeccably fulfill their duty, following their dharma, without attachment to the results of their actions, doing everything as an offering to God. The article emphasizes that the war in the "Bhagavad Gita" is a multifaceted symbol that encompasses not only the external physical battle but also the internal struggle of each person for self-awareness, true understanding of their dharma, and spiritual liberation. The publication also conveys the idea that in the context of the "Bhagavad-Gita," war represents not just a physical conflict, but a symbol of spiritual struggle. The external conflict is merely a reflection of the internal, spiritual one. The entire "Bhagavad Gita" can be perceived as an allegory of a person's struggle with their own passions, attachments, illusions, and delusions. The article draws parallels between the teachings of the "Bhagavad Gita" and the issues of the contemporary Russian-Ukrainian war. The Russian-Ukrainian war is examined in the context of the "Bhagavad Gita" through several key concepts of this classic Indian sacred text. Particular attention is drawn to the fact that in the "Bhagavad-Gita," special emphasis is placed on ethics, the fulfillment of duty (dharma), the struggle between good and evil, as well as the issue of inner conflict and the importance of spiritual choice, even in the most challenging situations.